2015
DOI: 10.1016/j.jretai.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Multi-channel Retail Mix on Online Store Choice: Does Online Experience Matter?

Abstract: More and more grocery retailers are becoming multi-channel retailers, as they are opening an online alternative next to their traditional offline supermarkets. While the number of multi-channel grocery shoppers is also expanding at a fast growth rate, there are still large differences in online shopping frequency, and as a result, in the levels of experience with buying in the online grocery channel. This study wants to (i) identify the underlying drivers of online store choice and (ii) explore if and how thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
214
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(232 citation statements)
references
References 58 publications
5
214
0
13
Order By: Relevance
“…(1) and (2), we acknowledge two issues. First, a household's decision to shop online with a particular chain is not exogenous; households tend to choose the online store hosted by the chain that they prefer offline (Melis et al 2015). A potential self-selection thus arises, because the dependent variable influences this explanatory variable, which could lead to biased estimates.…”
Section: Methodsmentioning
confidence: 99%
“…(1) and (2), we acknowledge two issues. First, a household's decision to shop online with a particular chain is not exogenous; households tend to choose the online store hosted by the chain that they prefer offline (Melis et al 2015). A potential self-selection thus arises, because the dependent variable influences this explanatory variable, which could lead to biased estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Multi-channel clothing shoppers may initially search for information at online stores and then shop at a brick-and-mortar store, or vice versa (Melis, Campo, Breugelmans, & Lamey, 2015). Thus multi-channel retailing has evolved into omni-channel retailing, in which online and offline channels are integrated to provide consumers with seamless shopping experiences.…”
Section: Clothing Retail Channelsmentioning
confidence: 99%
“…However, the lack of consumer trust often associated with online retail represents a significant barrier to such customer acquisition (Benedicktus et al 2010;Schlosser, White, and Lloyd 2006). Consumer distrust of online vendors is particularly problematic for first-time purchases, because consumers have no direct experience with which to assess the retailer's trustworthiness (Melis et al 2015;Schlosser, White, and Lloyd 2006;Singh and Sirdeshmukh 2000;Yoon 2002). The challenge faced by online retailers in establishing trust online is highlighted by survey research that found 60% of US Internet users are extremely or very concerned about scams and fraud related to online shopping, which represents a six percent increase in that figure from two years prior (Microsoft 2014).…”
mentioning
confidence: 99%